Improving Learning Outcomes About Faith in The Apostles Through Group Discussion Methods in Grade 4 Elementary School Children - Reki Novendra (BiCED Proceeding, 2024)
This study aims to improve students' learning outcomes on the material of Belief in the Prophets of Allah through the implementation of the Problem-Based Learning model in Cycle I and the Project-Based Learning model in Cycle II. This research uses the Classroom Action Research (CAR) design, conducted in two cycles with different teaching models. In Cycle I, the Problem-Based Learning model with group discussion methods was applied, while in Cycle II, the Project-Based Learning model involving the creation of a poster about the exemplary traits of the Prophet was used. The results indicate an improvement in students' understanding and engagement in learning, as reflected by the increased learning outcomes in Cycle II, with 100% of students meeting the Minimum Completion Criteria (KKM). However, several students in Cycle I did not meet the KKM due to difficulties in understanding the material and limited discussion time. Reflections from both Cycles I and II provide a basis for improvements in future teaching implementations, such as adjusting assessment questions and increasing discussion time.